Removal of carbamates and detoxification potential in a biomixture: Fungal bioaugmentation versus traditional use - Rodríguez Rodríguez, Carlos E. (2017)
The use of fungal bioaugmentation represents a promising way to improve the performance of biomixtures for the elimination of pesticides. The ligninolyitc fungus Trametes versicolor was employed for the removal of three carbamates (aldicarb, ALD; methomyl, MTM; and methiocarb, MTC) in defined liquid medium; in this matrix ALD and MTM showed similar half-lives (14 d), nonetheless MTC exhibited a faster removal, with a half-life of 6.5 d. Then the fungus was employed in the bioaugmentation of an optimized biomixture to remove the aforementioned carbamates plus carbofuran (CFN). Bioaugmented and non-bioaugmented systems removed over 99% ALD and MTM after 8 d of treatment, nonetheless a slight initial delay in the removal was observed in the bioaugmented biomixtures (removal after 3 d: ALD 87%/97%; MTM 86%/99%, in bioaugmented/non-bioaugmented systems). The elimination of the other carbamates was slower, but independent of the presence of the fungus: >98% for MTM after 35 d and >99.5% for CFN after 22 d. Though the bioaugmentation did not improve the removal capacity of the biomixture, it favored a lower production of transformation products at the first stages of the treatment, and in both cases, a marked decrease in the toxicity of the matrix was swiftly achieved along the process (from 435 to 448 TU to values <1TU in 16 d).